2012
DOI: 10.1073/pnas.1212676110
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of SIK1 abundance and stability is critical for myogenesis

Abstract: cAMP signaling can both promote and inhibit myogenic differentiation, but little is known about the mechanisms mediating promyogenic effects of cAMP. We previously demonstrated that the cAMP response element-binding protein (CREB) transcriptional target salt-inducible kinase 1 (SIK1) promotes MEF2 activity in myocytes via phosphorylation of class II histone deacetylase proteins (HDACs). However, it was unknown whether SIK1 couples cAMP signaling to the HDAC-MEF2 pathway during myogenesis and how this response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 42 publications
1
47
1
Order By: Relevance
“…Next, we purified a GST-tagged kinase-dead Wnd (GST-Wnd KD —K188A, to rule out autophosphorylation of Wnd) from E. coli and evaluated its phosphorylation by MTORC1 in vitro (Stewart et al, 2013). We found that GST-Wnd KD was phosphorylated only in the presence of MTORC1, and Torin1 significantly decreased this phosphorylation (Figures 5H–5I).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we purified a GST-tagged kinase-dead Wnd (GST-Wnd KD —K188A, to rule out autophosphorylation of Wnd) from E. coli and evaluated its phosphorylation by MTORC1 in vitro (Stewart et al, 2013). We found that GST-Wnd KD was phosphorylated only in the presence of MTORC1, and Torin1 significantly decreased this phosphorylation (Figures 5H–5I).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the inhibitory effect of cAMP/PKA on SIK activity, short-term exposure to the adenylyl cyclase activator Forskolin (Fsk) triggered the dephosphorylation of CRTC2/3, in control and SIK1-3 overexpressing HEK293T cells. In keeping with its short half-life, protein amounts of overexpressed SIK1 were decreased in comparison to SIK2 and SIK3 [34].…”
Section: Sik Activity Is Inhibited By Camp Signalingmentioning
confidence: 88%
“…Moreover, the myopathy was not rescued by rapamycin‐mediated inhibition of mTOR (data not shown), indicating that activation of the mTOR pathway is not responsible for the muscle pathology in the MyoD‐Lkb1 mice, and other downstream targets of Lkb1 may have mediated the phenotype. For example, the Lkb1 substrate SIK1 has been shown to regulate myogenesis through the class II HDACs . Further studies are needed to elucidate the exact mechanism that lead to the myopathy in the MyoD‐Lkb1 mice.…”
Section: Discussionmentioning
confidence: 99%